Adding value using sustainable building construction in Cyprus: the case study of the Cyprus University of Technology in Limassol - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Achillides, Zenon; Sofou, Souzanna; Philimis, Panayiotis; Hadjimits, Constandina G. (My University, 2013)
The building industry in Cyprus is in the midst of rapid change toward more sustainable design and construction. Sustainable or green building design is still an evolving field with rapid advances in knowledge, technology, and methods of measuring outcomes. The purpose of this study is to apply life cycle costing and assessment for buildings that make use of ‘new sustainable designs and technologies’ and compare directly the results obtained using the ‘existing traditional design’. This work will be supported by the case study of the Cyprus University of Technology performed in the framework of the ValPro European Project (Eracobuild VDP call). The case study of the Cyprus University of Technology provides a different perspective and highlights the potential increase of added value in real estate when involving extensive renovation and rehabilitation of older buildings to serve new functions within an existing city infrastructure.
Keywords: Sustainable Buildings; Eco-efficient technologies; Life cycle assessment; Costing; Value